LOGIKA PESAN KOMUNIKASI MUSIK DALAM LIRIK LAGU SMELLS LIKE TEEN SPIRIT - Ismail Taufik Rusfien (Universitas Pakuan, 2018)
AbstractCommunication is the process of delivering a message. Humans can share the experience they have in the form of music owned by its songwriter delivered to the recipient of the message. In September 2016, the music band Nirvana celebrates 25 years of the album called Nevermind. The famous song in the album is Smells Like Teen Spirit whose lyrics were created by Kurt Cobain lead singer and lead guitarist for the band. Qualitative research is subjective nature aims to determine the logic of the message in the lyrics of the song using the method of discourse analysis. The result of research in communications message shows the lyrics in the song logic expressive message comes from thoughts and feelings about the imperfections, teenage life, equality and freedom.Keywords: discourse analysis, song, music, logic message, communication